Test strategy risk in software testing / Atfina Naemah Omar @Omri - Omar @Omri, Atfina Naemah (2005)
Software testing is one of the most important techniques used to assure the quality of software products. Software testing keeps a high proportion during the whole software life cycle. In practice, software testing usually performed after code has been produced. This thesis presents the result of an empirical study of test strategy risk in software testing. The objective of this study is to identify differences of test strategy in software testing. Second objective is to analyze the risk in test strategy and the last objective is to identify which test strategy has low risk in software testing. Testing strategies is types of testing as distinct from testing techniques like module/component/unit testing, integration testing, function test, performance testing, acceptance test, and installation test. The author has distributed a set of questionnaires as the research instrument and conducted interview sessions with 19 selected respondents from various background and characteristic in order to get to get the primary data. Most of the respondent chooses black box testing as a testing strategy. Perhaps this research would contribute some idea to system tester in choosing the right testing strategy.